Advancing a rapid, high throughput screening platform for optimization of lentivirus production. Issue 10 (21st July 2021) - Gopal, Sneha; Osborne, Adam E.; Hock, Lindsay; Zemianek, Jill; Fang, Kun; Gee, Gretchen; Ghosh, Ronit; McNally, David; Cramer, Steven M.; Dordick, Jonathan S.
Abstract: Background: Lentiviral vectors (LVVs) hold great promise as delivery tools for gene therapy and chimeric antigen receptor T cell (CAR‐T) therapy. Their ability to target difficult to transfect cells and deliver genetic payloads that integrate into the host genome makes them ideal delivery candidates. However, several challenges remain to be addressed before LVVs are more widely used as therapeutics including low viral vector concentrations and the absence of suitable scale‐up methods for large‐scale production. To address these challenges, we have developed a high throughput microscale HEK293 suspension culture platform that enables rapid screening of conditions for improving LVV productivity. Key Results: High density culture (40 million cells mL −1 ) of HEK293 suspension cells in commercially available media was achieved in microscale 96‐deep well plate platform at liquid volumes of 200 μL. Comparable transfection and LVV production efficiencies were observed at the microscale, in conventional shake flasks and a 1‐L bioreactor, indicating that significant scale‐down does not affect LVV concentrations and predictivity of scale‐up. Optimization of production step allowed for final yields of LVVs to reach 1.5 × 10 7 TU mL −1 . Conclusions: The ability to test a large number of conditions simultaneously with minimal reagent use allows for the rapid optimization of LVV production in HEK293 suspension cells. Therefore, such a system may serve as a valuable tool in early stage process development and can be used as a screening tool to improve LVV concentrations for both batch and perfusion based systems. Graphical Abstract and Lay Summary: A high‐throughput, microscale screening platform for lentiviral vector production has been developed for rapid optimization of multiple plasmid transfection into various HEK293 suspension cell cultures. This work is the potential basis for rapid identification of optimal conditions for use in scale‐up of lentiviral vector production for gene therapy and related applications.